Prevalence of SARS-CoV-2 Antibodies Among Healthy Children From Colorado From 2020 to 2021: A Brief Report - Holly M. Frost; Cristy Geno Rasmussen; Hanan Shorrosh; Laura Pyle; Kimberly Bautista; Brigitte I. Frohnert; Marisa Stahl; Kimber Simmons; Andrea K. Steck; Xiaofan Jia; Liping Yu; Marian Rewers (SAGE Publishing, 2023)
There are few estimates of the seroprevalence of SARS-CoV-2 antibodies among children in the United States. We measured vaccine and infection induced seroprevalence among nearly 5000 healthy 1 to 17-year-old children in Colorado from 2020 to 2021. By December 2021, 89% of older children, ages 12 to 18, had antibodies detected. The increase was largely driven from vaccination rather than infection.